YOUTH PARTICIPATION IN DECISION-MAKING COMMITTEE AND DISCIPLINARY COMMITTEE AS CORRELATES OF COMMUNITY DEVELOPMENT IN SOUTH EAST, NIGERIA - Igwe, Sunday; Umezulike , N. A.; Amadi , U. P. N (Journal of Continuing and Development Education, 2024)
The study determined the relationship between youth participation in decision-making committee and disciplinary committee on community development in south east, Nigeria. Correlational design was used for this study. The targeted population for this study is 950 youth leaders from 95 local governments in south east Nigeria. The researcher targets 10 youth leaders from each local government area of each state that made-up south-east Nigeria. The sample for the study was 950 community youth leaders in the 95 local government areas in the five (5) states of south east. There were no sampling techniques since the population of the study is manageable and controllable by the researcher. Youth Participation in decision-making committee and Disciplinary Committee Questionnaire (YPDMCDCQ) and Community Development Questionnaire (CDQ)” were used for data collection. Two experts from the Department of Adult Education and one expert from the Department of Science Education validated the instruments, all from Michael Okpara University of Agriculture, Umudike. Cronbach alpha method was used to determine the reliability of the instrument which yielded an index of 0.75 for YPDMCDCQ and .81 for CDQ. Data collected were analysed using Pearson Product Moment Correlation Coefficient to answer the research questions while t-test was used to test the formulated null hypotheses at 0.05 level of significance. Based on the analysis, the findings of the study revealed that; Youth participation in decision-making committee significantly to a very high positive extent relate to community development in the South East Nigeria and that youth participation in disciplinary committee significantly to a very high positive extent relate to community development in the South-East Nigeria, based on the findings of the study, the researcher recommends that; Communities should ensure that youths should form a part of the components of their decision-making processes, that school administrators should collaborate with the morally-sound community youths in their respective host communities in enforcing discipline in their schools.